Scientific Journal Articles Output from Medical Doctoral Theses. A Comparative Study - Andrada Elena URDA-CÎMPEAN; Sorana Daniela BOLBOACĂ; Andrei ACHIMAŞ-CADARIU; Tudor C. DRUGAN (Applied Medical Informatics, 2016)
The scope of the present study was to contrast publication rates and particularities of original scientific articles related to medical PhD theses defended between 2009 and 2013 from one developing country (Romania) and two developed countries (France and the United Kingdom) within the European Union. A sample from each of the three countries was evaluated and then compared based on the journal type (national/international), time span between two consecutive articles from the same thesis, number of articles, journal impact factor and journal rank. The results of our quantitative analysis suggest that the majority of Romanian articles were published in Romanian journals, while French and the United Kingdom articles were published in greater proportions in journals outside the borders of their own country. The time span between two consecutive articles from the same thesis was similar for the three groups. Even though articles from Romanian theses were significantly more numerous than in those from France or the United Kingdom, they were published in less cited journals, according to their impact factor. Furthermore, most of the Romanian articles were published in the bottom half of the journals’ ranking, while the majority of articles from France or the United Kingdom were published in the top half of the ranking.